1998
DOI: 10.1002/chin.199847026
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Crystal Structure Studies by Single‐Crystal NMR Spectroscopy. 71Ga and 69Ga Single‐Crystal NMR of β‐Ga2O3 Twins.

Abstract: 1998 magnetic resonance, nuclear quadrupole resonance magnetic resonance, nuclear quadrupole resonance (solids and liquids) D 6560 -026Crystal Structure Studies by Single-Crystal NMR Spectroscopy. 71 Ga and 69 Ga Single-Crystal NMR of β-Ga 2 O 3 Twins.--(VOSEGAARD, T.; BYRIEL, I. P.; BINET, L.; MASSIOT, D.; JAKOBSEN, H. J.; J. Am. Chem. Soc. 120 (1998) 32, 8184-8188; Dep. Chem., Univ. Aarhus, DK-8000 Aarhus, Den.; EN)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 1 publication
5
5
0
Order By: Relevance
“…However, the crystal symmetry of b-Ga 2 O 3 single crystals used in our experiments was monoclinic, and not triclinic, based on NMR and previous EPR [14] studies. This result is consistent with those of Geller [3] and Vosegaard and colleagues [12], who found monoclinic symmetry of the b-Ga 2 O 3 crystal.…”
Section: Analysis and Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, the crystal symmetry of b-Ga 2 O 3 single crystals used in our experiments was monoclinic, and not triclinic, based on NMR and previous EPR [14] studies. This result is consistent with those of Geller [3] and Vosegaard and colleagues [12], who found monoclinic symmetry of the b-Ga 2 O 3 crystal.…”
Section: Analysis and Discussionsupporting
confidence: 92%
“…However, the b-Ga 2 O 3 :Cr 3+ single crystal used in our study did not have a twin structure, as confirmed by preliminary X-ray, NMR, and EPR experiments. Our NMR parameters for Ga nuclei in a crystal of b-Ga 2 O 3 doped with Cr 3+ were the same as those of Ga nuclei in the pure b-Ga 2 O 3 crystal [12], within experimental accuracy, as can be seen in Table 1. The influence of Cr 3+ (0.05 mol%) on Ga nuclei in the b-Ga 2 O 3 crystal is thus negligible.…”
Section: Analysis and Discussionsupporting
confidence: 73%
See 3 more Smart Citations